Ability of polymorphonuclear leukocytes to orient in gradients of chemotactic factors (The Rockefeller University Press, 1977)
Polymorphonuclear leukocyte (PMN) chemotaxis has been examined under conditions which allow phase microscope observations of cells responding to controlled gradients of chemotactic factors. With this visual assay, PMNs can be seen to orient rapidly and reversibly to gradients of N-formylmethionyl peptides. The level of orientation depends upon the mean concentration of peptide present as well as the concentration gradient. The response allows an estimation of the binding constant of the peptide to the cell. In optimal gradients, PMNs can detect a 1% difference in the concentration of peptide. At high cell densities, PMNs incubated with active peptides orient their locomotion away from the center of the cell population. This orientation appears to be due to inactivation of the peptides by the cells. Such inactivation in vivo could help to limit an inflammatory response.